Investing in Water Purification Infrastructure in an Emerging Market: Some Considerations for Impact Investors in South Africa - McCallum, Stephen; Viviers, Suzette; Ramírez, Rafael Robina (European Journal of Sustainable Development, 2019)
This study investigated the role that impact investors could play in the water purification infrastructure sector. Impact investors are individuals and institutions that invest in companies, organisations and funds with the aim of generating social and environmental impact alongside financial return. These investors are increasingly interested in emerging markets such as South Africa. As scholars have raised concerns about investors and companies profiting from the provision of a basic human right, the views of 20 experts were also gauged on this topic. Semi-structured personal interviews were conducted with key role players in the South African impact investment value chain (mostly investors) and the water provision system. Interviewees saw an important role for private sector investment in water purification infrastructure given government’s inability to meet the growing demand for potable water. Participants were, however, wary of private-public-partnerships and felt that investors and companies will only face a moral dilemma if they overcharge consumers for purified water. Impact investors should give careful consideration to domestic water users’ ability to pay as well as their needs and expectations. The development of a blended financing model is proposed. Keywords: Impact investing; emerging market; water purification infrastructure; South Africa; basic human rights; ethical concerns